Concomitant biohydrogen and poly-β-hydroxybutyrate production from dark fermentation effluents by adapted Rhodobacter sphaeroides and mixed photofermentative cultures. (October 2016) - Ghimire, Anish; Valentino, Serena; Frunzo, Luigi; Pirozzi, Francesco; Lens, Piet N.L.; Esposito, Giovanni
Graphical abstract: Highlight: Dark fermentation effluent was valorized via photofermentative H2 and PHB production. R. sphaeroides and mixed PNSB cultures were applied. H2 (256 mL H2 /g COD) and PHB (32.5% DCW) production was achieved from R. sphaeroides . More than 70% COD removal from DFE was achieved by mixed PNSB cultures. Abstract: This work aimed at investigating concomitant production of biohydrogen and poly-β-hydroxybutyrate (PHB) by photofermentation (PF) using dark fermentation effluents (DFE). An adapted culture of Rhodobacter sphaeroides AV1b (pH 6.5, 24 ± 2 °C) achieved H2 and PHB yields of 256 (±2) N mL H2 /g Chemical Oxygen Demand (COD) and 273.8 mg PHB/g COD (32.5 ± 3% of the dry cells weight (DCW)), respectively. When a diluted (1:2) DFE medium was applied to the adapted pure and mixed photofermentative culture, the respective H2 yields were 164.0 (±12) and 71.3 (±6) N mL H2 /g COD and the PHB yields were 212.1 (±105.2) and 50.7 (±2.7) mg PHB/g COD added, corresponding to 24 (±0.7) and 6.3 (±0) % DCW, respectively. The concomitant H2 and PHB production from the PF process gave a good DFE post treatment achieving up to 80% COD removal from the initial DFE.